Victims and perpetrators of male sexual assault - Hodge, Samantha (Journal of interpersonal violence, 1998)
Within the literature, two differing accounts of male sexual assault are hypothesized-one is the view that it is perpetrated by offenders who are characteristically homosexual, and the other that it is an example of heterosexual violence. Two studies were conducted that explored these opposing possibilities. The first was an analysis of data collected from two sources-83 victim self-report questionnaires and review of 36 investigated police reports. The results indicated that homosexual offenders were more likely to have known their victims for some time and target those under the age of 25. Heterosexual offenders tended to attack strangers of all ages and were more likely to operate in gangs. A comparison of the two samples indicated that the acquaintance sexual assault was less likely to be reported to the police, drawing attention to the fact that differing explanations may be strongly influenced by the particular sample under study